2000
DOI: 10.1097/00001756-200002280-00040
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors modulate effects of C-section birth on dopaminergic function in the rat

Abstract: Genetic predisposition and environmental factors such as perinatal complications are believed to contribute to the etiology of schizophrenia, a disorder involving enhanced CNS dopaminergic activity. This study used a rat model to test whether genetic factors and a minor birth complication, i.e. Caesarean section (C-section) birth, interact in producing longterm effects on dopamine-mediated behavior. For this, we compared the effects of vaginal and C-section birth on amphetamine (AMPT)-induced locomotor activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Neurodevelopmental animal models include maternal immune activation, prenatal malnutrition, the interruption of neurogenesis by methylazoxymethanol (MAM) and the neonatal ibotenic acid lesion of the ventral hippocampus 113,114 . Additional models are represented by the exposure of pregnant mice to unpredictable stress, maternal separation or birth complications [115][116][117] . All of these models have revealed behavioural deficits associated either with positive, cognitive or negative symptoms of schizophrenia, and alterations in the dopaminergic, glutamatergic, GABAergic and serotonergic systems [118][119][120][121][122][123][124] .…”
Section: Vulnerability Of Our Youth: Neurodevelopmentmentioning
confidence: 99%
“…Neurodevelopmental animal models include maternal immune activation, prenatal malnutrition, the interruption of neurogenesis by methylazoxymethanol (MAM) and the neonatal ibotenic acid lesion of the ventral hippocampus 113,114 . Additional models are represented by the exposure of pregnant mice to unpredictable stress, maternal separation or birth complications [115][116][117] . All of these models have revealed behavioural deficits associated either with positive, cognitive or negative symptoms of schizophrenia, and alterations in the dopaminergic, glutamatergic, GABAergic and serotonergic systems [118][119][120][121][122][123][124] .…”
Section: Vulnerability Of Our Youth: Neurodevelopmentmentioning
confidence: 99%
“…For example, two studies revealed that birth complications enhanced amphetamine-induced hyperlocomotion, thus providing support for the implication of obstetrical complications in the pathogenesis of schizophrenia (El-Khodor and Boksa, 1998; Vaillancourt and Boksa, 1998). A subsequent experiment determined that birth complications differentially affected amphetamine-induced hyperlocomotion in three rat strains, suggesting a genetic predisposition to the effects ofbirth insults (Berger et al, 2000). This paradigm has also been used in lesion studies to test neural substrates possibly involved in the development of schizophrenia.…”
Section: Amphetamine-induced Hyperlocomotionmentioning
confidence: 95%
“…They were housed in groups of [4][5][6][7][8][9][10][11][12] per cage in an animal room kept at 20-22 oC, with a relative humidity of 40% and a 12-hour light cycle (lights on 0800-2000h). Throughout their stay, mice had free access to standard mouse chow and water.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Berger et al (Berger et al, 2000) compared the effects of vaginal and C-section birth on amphetamine (AMPT)-induced locomotor activity in different strains of rats. Amphetamine-induced locomotion was increased in Sprague-Dawley rats and reduced in Lewis rats after C-section birth as compared to vaginal birth.…”
Section: Gene-environment Interplaymentioning
confidence: 99%